On the performance of SC-FDE receivers for base station cooperation systems with rate-limited backhaul links - Ribeiro, F.
In this paper we consider BS (Base Station) cooperation schemes for the uplink of broadband wireless systems based on SC-FDE schemes (Single-Carrier with Frequency-Domain Equalization). We have up to P MTs (Mobile Terminals) transmitting simultaneously to R BSs and the signals received by each BS are send to a central unit that employs an iterative frequency-domain receiver to separate different MTs. To reduce the bit rate requirements at the backhaul links we sample and quantize the signals at each BS and the receiver is specially designed taking into account the adopted quantization scheme. We also propose a relatively simple, yet quite accurate analytical approach for obtaining the performance of the proposed receivers.